2011
DOI: 10.1080/17461391.2011.577240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EMG activity during stable and unstable push‐up protocols

Abstract: This experiment examined muscle activation measured using electromyography (EMG) during a standardized push-up performed on stable and unstable surfaces. Fifteen highly trained participants performed four push-ups: standard (hands and feet on the floor), either the hands or feet on an unstable surface (single instability), and with both hands and feet on unstable surfaces (dual instability). Unstable surfaces were created using a stability ball and an extreme balance board. EMG activity was recorded from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 28 publications
1
44
0
4
Order By: Relevance
“…Training on unstable surfaces, exposing individuals to altered sensory input, is reported to increase muscular stress (Anderson et al, 2013) and may lead to gains in stability, proprioceptor activity, sway control, and improved core stability through neuro-adaptive mechanisms (Aggarwal et al, 2010;Schilling et al, 2009;McNeill, 2010). Anderson et al (2013) recently demonstrated that as the level of instability increased during a push-up protocol, there was a greater amount of muscle activation for the core stabilizers, prime movers and lower body stabilizers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Training on unstable surfaces, exposing individuals to altered sensory input, is reported to increase muscular stress (Anderson et al, 2013) and may lead to gains in stability, proprioceptor activity, sway control, and improved core stability through neuro-adaptive mechanisms (Aggarwal et al, 2010;Schilling et al, 2009;McNeill, 2010). Anderson et al (2013) recently demonstrated that as the level of instability increased during a push-up protocol, there was a greater amount of muscle activation for the core stabilizers, prime movers and lower body stabilizers.…”
Section: Discussionmentioning
confidence: 98%
“…Surface EMG recording locations were measured from five muscle groups (Anderson et al, 2013;Behm et al, 2002;Cram et al, 1998); Rectus Abdominus (muscle bellies lateral to the umbilicus), Internal Obliques (2.5 cm medial from the anterior superior iliac spine), Erector Spinae (2 cm lateral to L5-S1), Bicep Femoris (mid-belly of the long head), Soleus (mid-point between medial malleolus and medial condyle of the tibia). Each EMG site was shaved, cleansed with alcohol, and abraded with inter-electrode distances of approximately 2.5 cm positioned parallel to the orientation of the fibres being measured.…”
Section: Surface Electromyographymentioning
confidence: 99%
See 1 more Smart Citation
“…Por outro lado, não foram observadas diferenças na atividade dos músculos do core na prancha ventral com instabilidade dupla (PV-BGB e PV-BGD) em comparação a instabilidade simples com bola de ginástica (PV-BGS), contrastando com Anderson et al [8] , que demonstraram maior ativação do core no exercício flexão de braço com instabilidade dupla em relação a instabilidade simples.…”
Section: Discussionunclassified
“…While extensive research has investigated differences in initial hand placement, joint stresses and optimizing training effectiveness [6][7][8][9][10][11][12][13][14][15][16][17][18], little attention has been given to the changes in body position over the course of an extended push-up bout when compensational movement patterns are likely to be adopted. Therefore, the purpose of this article was to compare the natural push-up body positioning from the beginning to the end of a continuous 2-minute standardized push-up assessment.…”
Section: Introductionmentioning
confidence: 99%